EVALUASI PROGRAM MAN MODEL SEBAGAI UPAYA PENINGKATAN MUTU MADRASAH ALIYAH - Ahmad Darmadji (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2010)
The study aims to highlight the program impact of Development of Madrasah Aliyah Project (DMAP) through MAN (read: Madrasah Aliyah Negeri) Model for improving Madrasah Aliyah. The study was carried out in MAN Yogyakarta III (Mayoga) with qualitative approach. The data collection is through documentation, interview, observation, and open questionnaire. The study found that the DMAP program has been able to improve the output quality of the MAN Model indicated by the percentage increase of acceptance in state universities, i.e. 34.21% during DMAP and 46.83% after DMAP. In addition, students of MAN Model are able to obtain achievement as those of from Favorite Senior High School (read: SMA Unggulan).